2009
DOI: 10.1155/2009/845260
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Hyperplastic Polyp Associated with Proliferation of Xanthoma Cells Observed by Magnification Narrow-Band Imaging Endoscopy

Abstract: A case of gastric hyperplastic polyp with proliferation of xanthoma cells is reported. The patient was a 69-year-old man who visited our hospital for further evaluation of gastric polyps. Endoscopic examination of the upper digestive tract revealed multiple hyperplastic polyps in the gastric antrum. There was a pedunculated polyp with whitish yellow granules, 7 mm in diameter, arising from the greater curvature of the antrum. Magnification narrow-band imaging endoscopy (GIF-H260Z, Olympus) revealed long microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Most of the times no treatment is required13 14 but careful follow-up with endoscopy is needed to see its behaviour 15. In some reports, gastric xanthelasma has been treated with endoscopic mucosal resection in the presence of associated polyps 16. In some cases, endoscopic argon beam treatment showed good results and heat probe therapy was found to heal the lesions in almost all patients 17.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the times no treatment is required13 14 but careful follow-up with endoscopy is needed to see its behaviour 15. In some reports, gastric xanthelasma has been treated with endoscopic mucosal resection in the presence of associated polyps 16. In some cases, endoscopic argon beam treatment showed good results and heat probe therapy was found to heal the lesions in almost all patients 17.…”
Section: Discussionmentioning
confidence: 99%
“…There seem to be various possible causes underlying the development of xanthoma, such as an anomaly in lipid metabolism or inflammatory changes in the gastric mucosa. It has been reported that gastric xanthomas are accompanied by various gastric lesions including intestinal metaplasia [21], hyperplastic polyps [22], and gastric cancer [23]. A close relationship among gastric xanthoma, H. pylori infection, and atrophic gastritis was also reported [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of dyspepsia has been increasing, making it one of the primary reasons patients seek medical attention from gastroenterologists [ 5 ]. According to a review article published in the Journal of Gastroenterology & Hepatology , functional dyspepsia (i.e., stretching, contractions, and spasms of a structurally normal stomach causing symptoms) accounts for most cases of chronic dyspepsia [ 6 ]. In this article, we discuss a patient who required further investigation after failing first-line treatment for presumed functional dyspepsia.…”
Section: Discussionmentioning
confidence: 99%